Analysis of Consumer Satisfaction Levels on the Quality of Over the Counter Drug Services at Kamila Pharmacy (PT. LARPA JAYA PUBLISHER, 2025)
Satisfaction is a feeling of pleasure or disappointment that arises in a person after comparing impressions or perceptions of someone's performance or the results of a product, as well as expectations. The research objective is to determine the level of patient satisfaction with pharmaceutical services at Kamila Pharmacy. This research is descriptive research. The sample in this study consisted of 100 respondents at Kamila Pharmacy. The technique used was purposive sampling. The research results show that in the reliability aspect of drug information services, almost all respondents or 42% of respondents stated they were very satisfied and 45% of respondents stated they were satisfied, followed by quite satisfied at 9.2%, dissatisfied at 2.6%, and very dissatisfied at 1.2%. In the responsiveness aspect of drug information services, almost all respondents or 50% of respondents stated they were satisfied and 37% of respondents stated they were very satisfied, followed by quite satisfied at 7.6%, dissatisfied at 3.2%, and very dissatisfied at 2.2%. In the assurance aspect of drug information services, almost all respondents or 76% of respondents stated they were very satisfied and 19.5% of respondents stated they were satisfied, followed by quite satisfied at 3.25%, dissatisfied at 0.75%, and very dissatisfied at 0.5%. In the empathy aspect of drug information services, almost all respondents or 48.25% of respondents stated they were very satisfied and 42% of respondents stated they were satisfied, followed by quite satisfied at 6.25%, dissatisfied at 2.5%, and very dissatisfied at 1%. In the physical facilities aspect of drug information services, almost all respondents or 30.6% of respondents stated they were very satisfied and 51.2% of respondents stated they were satisfied, followed by quite satisfied at 11.4%, dissatisfied at 4.4%, and very dissatisfied at